Successful placement of a tunnelled hemodialysis catheter in persistent left superior vena cava: a case report and literature review - Patel, Maulik; Dholakia, Akash (International Journal of Research in Medical Sciences, 2026)
Persistent left superior vena cava (PLSVC) is the most common congenital thoracic venous anomaly and is often detected incidentally during central venous procedures. Its presence may complicate hemodialysis catheter placement because of the unusual venous anatomy and potential risk of catheter malposition or arrhythmia. We report the case of a 56-year-old man with end-stage renal disease secondary to diabetes mellitus and hypertension who required urgent hemodialysis. Ultrasound examination revealed thrombosis of the right internal jugular vein, necessitating left-sided vascular access. During tunneled hemodialysis catheter insertion, fluoroscopy demonstrated an unexpected guidewire course along the left mediastinal border. Contrast venography confirmed a PLSVC draining into a dilated coronary sinus and subsequently into the right atrium. Given the favorable drainage pattern, a cuffed dual-lumen tunneled hemodialysis catheter was successfully inserted under fluoroscopic guidance without procedural complications. The catheter achieved blood flow rates of 250–300 ml/min with satisfactory dialysis adequacy (Kt/V >1.2). No arrhythmia, catheter dysfunction, thrombosis, infection, or hemodynamic instability occurred during the procedure or throughout 3 months of follow-up. This case highlights the importance of recognizing an unexpected left-sided guidewire trajectory during venous access procedures and promptly confirming the anatomy before catheter advancement. When right atrial drainage is established, tunneled hemodialysis catheter placement through a PLSVC can provide safe and effective dialysis access in patients with limited vascular options.